Safety Evaluation of Multiple Strains of Lactobacillus plantarum and Pediococcus pentosaceus in Wistar Rats Based on the Ames Test and a 28-Day Feeding Study - Cheng-Chih Tsai; Sew-Fen Leu; Quan-Rong Huang; Lan-Chun Chou; Chun-Chih Huang (The Scientific World Journal)
Three lactic acid bacterial strains, Lactobacillus plantarum, HK006, and HK109, and Pediococcus pentosaceus PP31 exhibit probiotic potential as antiallergy agents, both in vitro and in vivo. However, the safety of these new strains requires evaluation when isolated from infant faeces or pickled cabbage. Multiple strains (HK006, HK109, and PP31) were subject to a bacterial reverse mutation assay and a short-term oral toxicity study. The powder product exhibited mutagenic potential in Salmonella Typhimurium strains TA98 and TA1535 (with or without metabolic activation). In the short-term oral toxicity study, rats received a normal dosage of 390 mg/kg/d (approximately 9×109 CFU/kg/d) or a high dosage of 1950 mg/kg/d (approximately 4.5×1010 CFU/kg/d) for 28 d. No adverse effects were observed regarding the general condition, behaviour, growth, feed and water consumption, haematology, clinical chemistry indices, organ weights, or histopathologic analysis of the rats. These studies have demonstrated that the consumption of multiple bacterial strains is not associated with any signs of mutagenicity of S. Typhimurium or toxicity in Wistar rats, even after consuming large quantities of bacteria.